House of Abraham [videorecording (DVD)] - Hassel, Lukas; Henstridge, Natasha; Shaye, Lin, 1943-; Hassel, Lukas (Jump Rock Pictures, 2026)
A woman looking for an end to her suffering, checks in to the House of Abraham, home to a mysterious cult that promises a way out. She soon discovers all is not what it seems and must plan an escape before it's too late.